Antibiotics affected the bacterial community structure and diversity in pore water and sediments with cultivated Phragmites australis in a typical Chinese shallow lake - Zhang, Ling; Bai, Junhong; Zhai, Yujia; Zhang, Kegang; Wei, Zhuoqun; Wang, Yaqi; Liu, Haizhu; Xiao, Rong; Jorquera, Milko A. (Frontiers in Microbiology, 2023)
The migration of antibiotics and bacterial communities between sediments and pore water occurring in the lake, which is affected by aquatic vegetation. However, the differences in bacterial community structure and biodiversity between pore water and sediments with plants in lakes under antibiotic stress are still poorly understood. We collected pore water and sediments in both wild and cultivated Phragmites australis regions in the Zaozhadian (ZZD) Lake to explore the characteristics of the bacterial community. Our results showed that the diversity of bacterial community in sediment samples were significantly higher than those in pore water samples in both P. australis regions. Due to higher antibiotic levels in sediments from the cultivated P. australis region, the composition of bacterial communities showed a difference, which reduced the relative abundance of dominant phyla in pore water and increased that in sediments. The higher bacterial variations in pore water could be explained by sediment in the cultivated P. australis region than that in wild P. australis region, therefore plant cultivation might change the source-sink pattern between sediments and pore water. The dominant factors shaping the bacterial communities in the wild P. australis region pore water or sediment were NH4-N, NO3-N, and particle size, while cultivated P. australis region pore water or sediment were oxytetracycline, tetracycline, etc. The findings of this work indicates that the antibiotic pollution caused by planting activities has a greater impact on the bacterial community, which will provide a reference for the use and management of antibiotics in lake ecosystems.